KARAKTERISTIK PERMUKIMAN DI TEPIAN SUNGAI: Studi Kasus: Permukiman di Tepian Sungai Musi - Sastika, Anta; Yasir, Abdul (Talenta Publisher, 2017)
Musi River is the lifeblood of Palembang’s resident since the day kingdom of Sriwijaya. The existence of the Musi river becomes important in public life Palembang’s of resident. . Palembang city grow and develop from the banks of the Musi river. It can be seen from the structure of spatial and settlement and patterns of social life of the people which were originally all the old village oriented to the river and make the river as part of the livelihood changes and moves away from the river. Its resulted in morphological changes of space Palembang which originally Musi river as the front into the rear. As is general, the banks of the river into a desenly populated area and tend rundown. This condition is one of the causes few problems. Therefore, this research takes place on the banks of the Musi river whick crosses the city of Palembnag. This study of the research uses quaoitative research process to produce descriptive data in the form of words orspoken as a from of policy. This research’s approach is rationalistic with comparative theory settlements. This research is a study of the characteristics of settlement patterns by looking at the structure of the settelement pattern is an orientation initially Musi river settelement patterns that change with the development of infrastructure.